Formal characteristics of portable emergency shelters - Assmaa Muhammed Al-muqramm; Zaineb Saad Mahdi Mahdi (Iraqi Journal of Architecture and Planning, 2019)
Wars and natural disasters have long been a threat to human life in many ways, including the destruction and loss of housing and other buildings, which made it necessary to develop rapid shelter plans to reduce the disaster. Plans to rebuild affected areas often take a long time, forcing those affected to take temporary solutions without regard to utility and durability. The shelters were designed in different types according to need. The previous knowledge dealt with a variety of species that could be categorized into simple and complex shelters. The first included shelters that could be carried by humans and the other carried by different means of transportation. The materials used in manufacturing, It has a portable shelter such as flexibility, the possibility of integration and rigging of the structure, adaptation, self-sufficiency and other characteristics. The research problem was focused on "the cognitive need to explore the formal characteristics of portable emergency shelters". The aim of the research is to identify the formal characteristics of the portable shelter that distinguish it from other types of portable architecture. It ensures the efficiency and durability of the shelter in performing its functions . This requires a three-stage approach. The first is to construct a theoretical framework on the morphological properties of the portable shelter and to explore the nature of the vocabulary and indicators of the formal characteristics of portable shelters. These include visual properties, dimension characteristics, description and analysis of two-dimensional surfaces, three-dimensional building block Design). The second is to examine these vocabulary within selected samples, and thirdly to discuss the results and conclusions that thus reinforce the theoretical framework of the vocabulary.